The Influence of Reward Strategies, Management Behavior, and Remuneration on the Work Motivation of State Aliyah Madrasah Teachers in Jambi Province - Elviana Elviana; Mukhtar Mukhtar; Kasful Anwar Us (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the influence of reward strategies, management behavior, and remuneration on the work motivation of Madrasah Aliyah Negeri (MAN) teachers in Jambi Province, both partially and simultaneously, as well as directly or indirectly. Using a quantitative approach with a survey method of 145 teachers and analyzed by path analysis, this study shows that the three independent variables have a significant effect on teachers' work motivation. Key findings include the direct influence of reward strategies and management behaviors on remuneration and work motivation, as well as indirect influences through remuneration. Overall, the results indicate that the better the reward strategy, management behavior, and remuneration, the higher the teacher's motivation to work.